Lithium Toxicity and PRES: A Novel Association. Issue 1 (26th February 2014) - Fitzgerald, Ryan T.; Fitzgerald, Caris T.; Samant, Rohan S.; Kumar, Manoj; Ramakrishniah, Raghu; Van Hemert, Rudy; Angtuaco, Edgardo J.
ABSTRACT We report two cases of posterior reversible encephalopathy syndrome (PRES) occurring in association with supra‐therapeutic serum lithium levels. Although the neurologic manifestations of lithium toxicity are well known, this is, to our knowledge, the first report describing a link between lithium toxicity and PRES. We discuss the current understanding of the pathogenesis of PRES and suggest mechanisms by which lithium may play a role in its development.